Using Soft Power in Constructing Attitudes of Gender in “A Streetcar Named Desire” - Jassim, Aseel Ahmed; Almaaroof, Ansam Riyadh Abdullah (Journal of Ecohumanism, 2024)
This essay looks at how Tennessee Williams’s beloved drama "A Streetcar Named Desire" uses the idea of soft power to limit and mold society perceptions of gender identity and performance. Based on Judith Butler’s seminal theory—which holds that gender is a socially created and performative act rather than an underlying essence—this analysis shows how the play uses soft power to enforce standards of acceptable gender expression.. The protagonist, Blanche DuBois, embodies the typical Southern belle, yet her brother-in-law Stanley Kowalski’s blatantly masculine instincts conflict with her attempts to maintain a rigorously feminine persona. This study demonstrates how Williams quietly challenges restrictive gender norms by stressing their repressive and harmful effects on people who fail to properly "perform" their given roles. This is done through an analysis of the play’s character relationships, dialogue, and dramatic tensions. The study contends that "A Streetcar Named Desire" uses a sort of soft power that subverts viewer notions about gender identity by showing the tragic collapse of Blanche, who is shunned for her incapacity to convincingly execute the anticipated feminine script. A significant case study at the nexus of literature, gender studies, and the sociology of power dynamics, the play contributes to the larger societal discourses and power structures that govern permissible ways of gender expression.. This study offers insights into how cultural production shapes, reinforces, or subverts societal views about the performative nature of gender identity through an analysis of how "A Streetcar Named Desire" uses soft power to control attitudes of gender.